2015
DOI: 10.1111/luts.12086
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Mediating the Relationship Between Symptom Severity and Health‐Related Quality of Life in Patients with Lower Urinary Tract Symptoms

Abstract: In order to enhance HRQOL, LUTS interventions should address the mental health of patients in addition to providing physical relief of symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“…Our findings suggest that the underpinning of holistic well‐being within vulnerable health contexts lies in maintaining positive health behaviours with emotional stability. In order to enhance HRQOL of people with chronic health conditions, interventions should address the mental health in addition to providing physical relief of symptom (Choi, Lam, & Chin, 2016; Choi, Wan, Kwok, Chin, & Lam, 2019), which may be achieved through psychologically informed physical exercises. This finding conforms to the recent increasing attention on and popularity of accommodative coping and acceptance‐based strategies for chronic illness rehabilitation, in particular, mindfulness‐based exercise interventions for people with chronic pain, neurodegenerative and musculoskeletal disorders (Kwok, Choi, & Chan, 2016; Kwok et al., 2019; McCracken, Carson, Eccleston, & Keefe, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that the underpinning of holistic well‐being within vulnerable health contexts lies in maintaining positive health behaviours with emotional stability. In order to enhance HRQOL of people with chronic health conditions, interventions should address the mental health in addition to providing physical relief of symptom (Choi, Lam, & Chin, 2016; Choi, Wan, Kwok, Chin, & Lam, 2019), which may be achieved through psychologically informed physical exercises. This finding conforms to the recent increasing attention on and popularity of accommodative coping and acceptance‐based strategies for chronic illness rehabilitation, in particular, mindfulness‐based exercise interventions for people with chronic pain, neurodegenerative and musculoskeletal disorders (Kwok, Choi, & Chan, 2016; Kwok et al., 2019; McCracken, Carson, Eccleston, & Keefe, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that mental health is a mediating factor in the relationship between LUTS severity and HRQOL. In other words, LUTS severity affects mental health, which in turn impairs HRQOL [ 7 ]. One major limitation of that study was its cross-sectional design.…”
Section: Introductionmentioning
confidence: 99%
“…Lower urinary tract symptoms (LUTS) are a leading cause of burden to health‐related quality of life (HRQOL) (Choi et al . , ) and mental health (Choi et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Lower urinary tract symptoms (LUTS) are a leading cause of burden to health-related quality of life (HRQOL) (Choi et al 2014a(Choi et al , 2016a and mental health (Choi et al 2016b). The global prevalence of LUTS was reported to be 45Á2% in both males and females in 2008 (Irwin et al 2011) and it is estimated that by 2018, 2Á3 billion people worldwide will have LUTS (Irwin et al 2011).…”
Section: Introductionmentioning
confidence: 99%